FORGOTTEN PRINCIPLES: HOW THE DIGITAL AGE TRANSFORMED THE HUMAN CONNECTION TO PHOTOGRAPHY (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
The goal of this paper is to explore the human connection to photography and examine the different principles that have been impacted by digital advancements in photography. This paper will investigate these principles and how they affect the perception of the beauty seen in photographs. The investigation of these principles builds upon Adrian Bejan's acclaimed book, 'Time and Beauty,' and the principles outlined in Constructal Law.
Keywords: Photography; Human development; Perception; Scan; Light